Not Only for Reading: Váchal’s Game with the Idea of “Beautiful Books” - Gawarecka, Anna (Porównania, 2021)
Josef Váchal (1884–1969), a graphic artist, painter and writer, primarily a xylographer, was considered as an outsider (and in his era “great absent”) of the 20th century Czech culture. Although it is almost impossible to enumerate all the areas in which this eccentric “multiartist” worked, however, at the center of his interests was the idea of a book entirely (from text to bookbinding) made by one artist. Most of the researchers who study Váchal’s book-making activity emphasize its connections with secessionist universalism, Wagner’s concept of Gesamtkunstwerk and the concept of “beautiful books”. The stylizing ambitions of this eccentric graphic artist found their fullest reflection in his impressively rich (covering several dozen titles)and a very diverse book design. Apart from his own occult studies and xylographic textbooks and written esoteric or heretical “secret” prints from centuries ago, he also published essayistic, poetic and novel texts, providing them with illustrations or rather supplementing the meanings conveyed by the written texts with meanings generated by the image, turning his book artifacts into objects of the intersemiotic way of reception.